The Establishment of a National Tissue Bank for Inflammatory Bowel Disease Research in Canada - Stephen M Collins; Kevin McHugh; Ken Croitoru; Micheal Howorth (Canadian Journal of Gastroenterology)
The Crohn’s and Colitis Foundation of Canada (CCFC) has established a national bank for tissue, serum and blood from patients with inflammatory bowel disease (IBD). Investigators from across the country submit material to the bank together with clinical data. Investigators may access their own patient information from the bank for their own study purposes, but the distribution of tissue is restricted to specific CCFC-funded projects. Currently, tissues are being collected from newly diagnosed, untreated IBD patients to support a recent initiative aimed at characterizing microbes in colonic and ileal biopsies from such patients. In the future, criteria for the submission of tissue will be tailored to specific research questions. This bank is believed to be the first national bank of its kind dedicated to research in Crohn’s disease and ulcerative colitis.